Export Promotion and Firm Entry and Survival in Export Markets - Lederman, Daniel (Taylor and Francis, 2016)
Surveys of export promotion agencies suggest that that they tend to focus on helping firms become exporters as a means to stimulate aggregate export growth, but the existing empirical evidence has paid little attention to the role of export promotion agencies in helping entry into exporting. This paper fills this gap with a panel of exporting and non-exporting firms from seven Latin American countries during the period 2006–2010. The results suggest that export promotion encourages exports mainly by helping firms enter into and survive in export markets. The impact on the intensive margin of exporting firms is not robust.